When a Circle Becomes the Letter O: Young Children’s Conceptualization of Learning and Its Relation With Theory of Mind Development - Wang, Zhenlin; Frye, Douglas A. (Frontiers in Psychology, 2021)
In two independent yet complementary studies, the current research explored the developmental changes of young children’s conceptualization of learning, focusing the role of knowledge change and learning intention, and its association with their developing theory of mind (ToM) ability. In study 1, 75 children between 48 and 86 months of age (M = 65.45, SD = 11.45, 36 girls) judged whether a character with or without a genuine knowledge change had learned. The results showed that younger children randomly attributed learning between genuine knowledge change and accidental coincidence that did not involve knowledge change. Children’s learning judgments in familiar contexts improved with age and correlated with their ToM understanding. However, the correlation was no longer significant once age was held constant. Another sample of 72 children aged between 40 and 90 months (M = 66.87, SD = 11.83, 31 girls) participated in study 2, where children were asked to judge whether the story protagonists intended to learn and whether they eventually learned. The results suggested that children over-attributed learning intention to discovery and implicit learning. Stories with conflict between the learning intention and outcome appeared to be most challenging for children. Children’s intention judgment was correlated with their ToM understanding, and ToM marginally predicted intention judgment when the effect of age was accounted for. The implication of the findings for school readiness was discussed. Training studies and longitudinal designs in the future are warranted to better understand the relation between ToM development and children’s learning understanding.